Defoliation by pastoralists affects savanna tree seedling dynamics by limiting the facilitative role of canopy cover. Issue 5 (1st July 2015) - Bufford, Jennifer L.; Gaoue, Orou G.
Abstract : Recurrent tree defoliation by pastoralists, akin to herbivory, can negatively affect plant reproduction and population dynamics. However, our understanding of the indirect role of defoliation in seedling recruitment and tree–grass dynamics in tropical savanna is limited. In West African savanna, Fulani pastoralists frequently defoliate several fodder tree species to feed livestock in the dry season. We investigated the direct and indirect effects of recurrent defoliation of African mahogany ( Khaya senegalensis ) by Fulani people on seedling (<2 cm basal diameter) and sapling dynamics in West Africa using four years of demographic data on seedling and sapling density, growth, and survival, coupled with fruit production and microhabitat data over the same time period. Tree canopy cover facilitated seedlings but had negative effects on sapling growth possibly via intraspecific competition with adult plants. Interspecific competition with grasses strongly reduced seedling survival but had a weak effect on sapling growth. Fire reduced seedling survival and weakly reduced growth of seedlings and saplings, but did not affect sapling survival. These results indicate that the effect of fire on seedlings and saplings is distinct, a mechanism suitable for an episodic recruitment of seedlings into the sapling stage and consistent with predictions from the demographic bottleneck model. Defoliation affected seedling density and sapling growth through changes in canopy cover, but had no effect on seedling growth and sapling survival. In the moist region, sapling density was higher in sites with low‐intensity defoliation, indicating that defoliation may strengthen the tree recruitment bottleneck. Our study suggests that large‐scale defoliation can alter the facilitative role of nurse trees on seedling dynamics and tree–sapling competition. Given that tree defoliation by local people is a widespread activity throughout savanna–forest systems in West Africa, it has the potential to affect tree–grass coexistence. Incorporating the influence of large tree defoliation into existing models of savanna dynamics can further our understanding of tree–grass coexistence and improve management. A rotating harvest system, which allows seedlings to recruit episodically, or a patchwork harvest, which maintains some nursery trees in the mosaic, could help sustain seedling recruitment and minimize the indirect effects of harvest.